A review on alkaline sulfite anthraquinone methanol as an alternative pulping process for non-woody biomass - Abdallah, Areej Fathelrahman; Jawaid, Mohammad; Mohamed, Ainun Zuriyati; Tahir, Paridah Md.; Osman, Fathelrahman Abdalla; Abdullah, Ummi Hani (Springer, 2023)
The manufacturing of pulps and papers from wood material via conventional processes has led to forest degradation, which has consequently caused adverse environmental impacts and disrupted the ecological balance. Hence, there has been an increased interest in using non-woody biomass as an alternative raw material for paper production. Alkaline sulfite anthraquinone methanol (ASAM) pulping process is cleaner, greener, and more environmentally, because the process does not involve sulfur compounds. It also offers better pulp and paper properties, especially for non-woody biomass. In the current review, pertaining to the production of high-quality papers and paperboards from non-woody biomass via ASAM pulping process was covered. Some of the non-woody biomass include kenaf, bamboo, elephant grass, jute, corn stalks, cotton stalks, and pearl millet stalks. As a whole, the ASAM pulping process exhibits higher pulp yield, delignification rate, and brighter, as well as enhanced pulping strength properties, with minimal air and water pollution. To the best of my knowledge, this review is the first in the field of this research. Therefore, this review highlighted the in-depth knowledge about the potentiality of non-woody biomass for pulp and paper production via ASAM pulping process.